2022
DOI: 10.1038/s41598-021-04649-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of ensemble machine learning algorithms on lifestyle factors and wearables for cardiovascular risk prediction

Abstract: This study looked at novel data sources for cardiovascular risk prediction including detailed lifestyle questionnaire and continuous blood pressure monitoring, using ensemble machine learning algorithms (MLAs). The reference conventional risk score compared against was the Framingham Risk Score (FRS). The outcome variables were low or high risk based on calcium score 0 or calcium score 100 and above. Ensemble MLAs were built based on naive bayes, random forest and support vector classifier for low risk and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…However, the Random Forest algorithm takes only a subspace of attributes into account when splitting a node. Trees can be more random when looking for the importance of the attribute randomly [45].…”
Section: Fig2 Random Forest Model With Three Treesmentioning
confidence: 99%
“…However, the Random Forest algorithm takes only a subspace of attributes into account when splitting a node. Trees can be more random when looking for the importance of the attribute randomly [45].…”
Section: Fig2 Random Forest Model With Three Treesmentioning
confidence: 99%
“…However, the random forest method takes only a subspace of attributes into account when splitting a node. Trees can be more random when looking for the importance of the attribute randomly [45].…”
Section: Fig2 Random Forest Model With Three Treesmentioning
confidence: 99%
“…The wearable devices have a reported sensitivity of more than 90% for detecting seizures [ 106 ]. Weiting et al used several algorithms, including SVM, RF, and naive Bayes, to build an ML algorithm ensemble for the purpose of predicting the cardiovascular risk from wearable healthcare data-collection devices [ 107 ]. In a study involving 407 participants using smartwatches, a gradient-boosting algorithm identified and predicted SARS-CoV2 infections [ 108 ].…”
Section: Role Of Machine Learning In Diagnosticsmentioning
confidence: 99%